Adverse and benevolent childhood experiences in Posttraumatic Stress Disorder (PTSD) and Complex PTSD (CPTSD): implications for trauma-focused therapies. Issue 1 (31st December 2020) - Karatzias, Thanos; Shevlin, Mark; Fyvie, Claire; Grandison, Graeme; Garozi, Maria; Latham, Emma; Sinclair, Michael; Ho, Grace Wing Ka; McAnee, Grainne; Ford, Julian D.; Hyland, Philip
ABSTRACT: Background: There is very little work on the role of positive or benevolent childhood experiences and how such events might offer protection from the insidious effects of adverse experiences in childhood or later in life. Objectives: We set out to test, using latent variable modelling, whether adverse and benevolent childhood experiences could be best described as a single continuum or two correlated constructs. We also modelled the relationship between adverse and benevolent childhood experiences and ICD-11 PTSD and Complex PTSD (CPTSD) symptoms and explored if these associations were indirect via psychological trauma. Methods: Data were collected from a trauma-exposed sample ( N = 275) attending a specialist trauma care centre in the UK. Participants completed measures of childhood adverse and benevolent experiences, traumatic exposure, and PTSD and CPTSD symptoms. Results: Findings suggested that adverse childhood experiences operate only indirectly on PTSD and CPTSD symptoms through lifetime trauma exposure, and with a stronger effect for PTSD. Benevolent childhood experiences directly predicted only CPTSD symptoms. Conclusions: Benevolent and traumatic experiences seem to form unique associations with PTSD and CPTSD symptoms. Future research is needed to explore how benevolent experiences can be integrated within existing psychological interventions to maximise recovery from traumatic stress.